INTERVENSI FISIOTERAPI TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DAN LUMBAR STABILIZATION UNTUK MENGURANGI NYERI DAN MENINGKATKAN LINGKUP GERAK SENDI (LGS) PADA KASUS LOW BACK PAIN E.C. HERNIA NUCLEUS PULPOSUS - Kurniani Fatma Hardini; Alfian Noha Zulkarnaen; Indra Cahyadinata; Dinda Aulya Saleabila (CV. ADIBA ADISHA AMIRA, 2024)
Lower Back Pain (LBP) e.c Herniated Nucleus Pulposus (HNP) is pain in the lower back that is localized or radicular because the nucleus pulposus is compressed by work factors and protrudes from the intervertebral disc, causing pain in the spine. In the long term, this causes immobilization, increases pain, decreases muscle strength, decreases LGS, and decreases functional performance. physiotherapy management in cases of LBP e.c HNP using Transcutaneal Electrical Stimulation (TENS) and Lumbar Stabilization. The method used a case study conducted at the Husada Asih YPAC Malang Clinic on 14-24. December 2022 with 4 meetings. The TENS dose used is symmetrical waves, frequency 20 Hz, pulse 330 ms and duration 20 minutes, with the aim of reducing pain. Lumbar stabilization exercise aims to increase joint range of motion, increase muscle strength, and improve functional performance. The conclusion of this case study is that physical therapy management of LBP e.c HNP cases using TENS techniques and lumbar stabilization reduces pain, increases joint range of motion, but does not increase muscle strength. and increases functional activity.